Gorczyciana sulawesica—a remarkable new plant bug genus and species(Heteroptera: Miridae: Cylapinae) from Indonesia - Wolski, Andrzej; Taszakowski, Artur (Zootaxa, 2023)
Gorczyciana gen. nov., a new remarkable genus of the subfamily Cylapinae, tribe Fulviini, is described from Indonesia. The new species Gorczyciana sulawesica sp. nov. from Sulawesi is documented with photographic images, SEM micrographs of the selected body parts, and female genitalic structures. Identification key to the cylapine tribes and genera of the tribe Fulviini of the Oriental Region is also given.